Understanding the impact of munia birds (Aves: Passeriformes: Estrildidae) on rice farming: Behavior, distribution, and bioacoustic parameters - AGUNG SIH KURNIANTO; NILASARI DEWI; NANANG TRI HARYADI; WILDAN ASSHIDIQI ARMA; REZA MAULANA; YURISKA HEPTA SARI; WANDA HAMIDAH; NUR LAILA MAGVIRA; AHMAD MUAMMAR KADAFI (Society for Indonesian Biodiversity, 2024)
Abstract. Kurnianto AS, Dewi N, Haryadi NT, Arma WA, Maulana R, Sari YH, Hamidah W, Magvira NL, Kadafi AM. 2024. Understanding the impact of munia birds (Aves: Passeriformes: Estrildidae) on rice farming: Behavior, distribution, and bioacoustic parameters. Biodiversitas 25: 186-196. Munia birds represent a significant challenge in rice farming. This study investigates the role of Munia birds (Aves: Passeriformes: Estrildidae) within rice agroecosystems. Utilizing point count observation methods in Desa Rowosari, Jember, across two farming models (organic and conventional), we assessed the behavior, population distribution, and bioacoustic parameters of Munia species. A total of 3820 Munia individuals were documented: 2187 Javan Munia (Lonchura leucogastroides Moore, 1858), 1214 Scaly-breasted Munia (Lonchura punctulate Linnaeus, 1758), and 419 White-capped Munia (Lonchura ferruginosa Sparrman, 1789). Bioacoustic recordings were conducted using the TASCAM DR 60D recorder, complemented by statistical tests in SPSS 16.0 and visual data representations via Matplotlib and Seaborn libraries. Findings revealed that Munias inflict damages ranging from 10.85% to 30% on rice crops. Notably, JM's bioacoustic bandwidth displayed adaptability between organic and conventional cultivation environments (P value=0.0129). In terms of population distribution, SbM has the highest population density on conventional (density=22.38), JM has the highest density on organic (density-32.55). Passing through activity is more observed in both types of organic and conventional management models. Scaly-breasted Munia dominates in three time groups, both in the morning (x ?= 224.75), mid day (x ?= 163.75), and afternoon (x ?= 198.25). However, PCA depiction indicates that the activity of passing through is dominated by JM. JM and SbM are depicted gathering in the center, indicating a similar average relationship between populations. While Munias pose potential threats as pests, their absence could surge insect populations, underscoring their ecological significance. This study accentuates the importance of an informed management strategy, considering Munia's multifaceted impact on agroecosystems.